Principal leadership according to the perspective of the Quran - Putra Mahendra Gunawan Nasution (Institute of Computer Science (IOCS), 2025)
Principal leadership in the modern era faces serious challenges, including moral degradation, character crisis, and the dominance of materialistic orientation in education management. Conventional leadership models often fail to form a school culture based on spiritual and ethical values. Therefore, a leadership approach is needed that is not only administratively effective, but also morally and spiritually strong. This study aims to examine the concept and implementation of principal leadership based on the perspective of the Qur'an by emphasizing the values ??of trust, justice, deliberation, and honesty as managerial and spiritual foundations. The method used is a qualitative descriptive research method through literature studies and content analysis of the verses of the Qur'an and related academic literature. The results of the study show that Quranic leadership contributes to forming an Islamic school culture, improving the quality of education management, strengthening the character of school residents, and becoming a solution to the crisis of moral leadership in the modern era. In conclusion, the Quranic leadership model based on divine values ??needs to be applied systematically in order to realize schools with character and civilization, although the development of quantitative instruments and in-depth digital integration is still needed.